2018
DOI: 10.1007/s40264-018-0699-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Utility of Social Media for Broad-Ranging Statistical Signal Detection in Pharmacovigilance: Results from the WEB-RADR Project

Abstract: Introduction and ObjectiveSocial media has been proposed as a possibly useful data source for pharmacovigilance signal detection. This study primarily aimed to evaluate the performance of established statistical signal detection algorithms in Twitter/Facebook for a broad range of drugs and adverse events.MethodsPerformance was assessed using a reference set by Harpaz et al., consisting of 62 US Food and Drug Administration labelling changes, and an internal WEB-RADR reference set consisting of 200 validated sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 20 publications
2
56
0
Order By: Relevance
“…Although future improvements to ADR recognition in social media posts in terms of performance and coverage may revise this recommendation, social media is not expected to become a first-line signal detection tool. It may, however, serve as a useful complement in specific niche areas [ 32 ]. Where an organisation decides on the use of social media data for signal detection and/or signal validation, the reporting of ADRs in the form of ICSRs should not be required as set out in GVP Module VI [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although future improvements to ADR recognition in social media posts in terms of performance and coverage may revise this recommendation, social media is not expected to become a first-line signal detection tool. It may, however, serve as a useful complement in specific niche areas [ 32 ]. Where an organisation decides on the use of social media data for signal detection and/or signal validation, the reporting of ADRs in the form of ICSRs should not be required as set out in GVP Module VI [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…The examination of SM utility in identifying AEs and SDRs has been previously performed by multiple groups, using various approaches. Some authors have concluded that SM should be further considered as a potential SD tool, while others concluded that SM shows a poor performance in AE and SDR identification . Although we count this work among the former group, we do not disagree with the core conclusions of the latter.…”
Section: Discussionmentioning
confidence: 52%
“…Some authors have concluded that SM should be further considered as a potential SD tool, 17,18 while others concluded that SM shows a poor performance in AE and SDR identification. 19,20 Although we count this work among the former group, we do not disagree with the core conclusions of the latter. Namely, we agree that SM cannot be used as a stand-alone data source and should not replace other pharmacovigilance activities.…”
Section: Discussionmentioning
confidence: 55%
“…12 Other potential applications for symptom data include adverse event monitoring, which has been shown to be feasible in social media data including Twitter. 13 However, caution must be used when considering Google data for this purpose as substantial scientific, 14…”
Section: Discussionmentioning
confidence: 99%